Novel Use of an Orbital Atherectomy Device for In-Stent Restenosis: Lessons Learned - K. Shaikh; S. Kelly; M. Gedela; V. Kumar; A. Stys; T. Stys (Case Reports in Cardiology)
We present a case of a 67-year-old man with stage III chronic kidney disease, uncontrolled diabetes mellitus, coronary artery disease, and high surgical risk who presented with two episodes of acute coronary syndrome attributed to in-stent restenosis (ISR) associated with heavily calcified lesions. In this case, we were able to improve luminal patency with orbital atherectomy system (OAS); however, withdrawal of the device resulted in a device/stent interaction, causing failure of the device. Given limitations in current evidence and therapies, managing ISR can be a technical and cognitive challenge. Balloon expansion of the affected region often provides unsatisfactory results, possibly related to significant calcium burden. OAS could be an efficacious way of reestablishing luminal patency in ISR lesions, as these lesions are often heavily calcified.